Optical Coherence Tomography and Its Role in Mohs Micrographic Surgery: A Case Report - C.Stanley Chan; Thomas E. Rohrer (Karger Publishers, 2012)
Optical coherence tomography (OCT) is an imaging technology with the potential to provide high-resolution images of the skin non-invasively. With this device, it is possible to identify a host of skin structures including tumors. In this case report, we demonstrate the use of an OCT device in delineating a lateral tumor margin of an ill-defined basal cell carcinoma prior to Mohs micrographic surgery. Following surgery, the OCT images are compared to histologic sections to confirm their accuracy. OCT technology has the potential to be a vital tool for dermatologists and particularly Mohs surgeons in identifying tumor margins and potentially reducing the number of invasive procedures needed.